The diagnostic challenge of progressive pseudorheumatoid dysplasia (PPRD): A review of clinical features, radiographic features, and WISP3 mutations in 63 affected individuals - ELÇİOĞLU, HURİYE NURSEL (WILEY, 2012)
Progressive pseudorheumatoid dysplasia (PPRD) is a genetic, non-inflammatory arthropathy caused by recessive loss of function mutations in WISP3 (Wnt1-inducible signaling pathway protein 3; MIM 603400), encoding for a signaling protein. The disease is clinically silent at birth and in infancy. It manifests between the age of 3 and 6 years with joint pain and progressive joint stiffness. Affected children are referred to pediatric rheumatologists and orthopedic surgeons; however, signs of inflammation are absent and anti-inflammatory treatment is of little help. Bony enlargement at the interphalangeal joints progresses leading to camptodactyly. Spine involvement develops in late childhood and adolescence leading to short trunk with thoracolumbar kyphosis. Adult height is usually below the 3rd percentile. Radiographic signs are relatively mild. Platyspondyly develops in late childhood and can be the first clue to the diagnosis. Enlargement of the phalangeal metaphyses develops subtly and is usually recognizable by 10 years. The femoral heads are large and the acetabulum forms a distinct lip overriding the femoral head. There is a progressive narrowing of all articular spaces as articular cartilage is lost. Medical management of PPRD remains symptomatic and relies on pain medication. Hip joint replacement surgery in early adulthood is effective in reducing pain and maintaining mobility and can be recommended. Subsequent knee joint replacement is a further option. Mutation analysis of WISP3 allowed the confirmation of the diagnosis in 63 out of 64 typical cases in our series. Intronic mutations in WISP3 leading to splicing aberrations can be detected only in cDNA from fibroblasts and therefore a skin biopsy is indicated when genomic analysis fails to reveal mutations in individuals with otherwise typical signs and symptoms. In spite of the first symptoms appearing in early childhood, the diagnosis of PPRD is most often made only in the second decade and affected children often receive unnecessary anti-inflammatory and immunosuppressive treatments. Increasing awareness of PPRD appears to be essential to allow for a timely diagnosis. (C) 2012 Wiley Periodicals, Inc.
Keywords: progressive pseudorheumatoid dysplasia; WISP3; joint pain; FAMILY-MEMBER WISP3; CHILDHOOD PPAC; RHEUMATOID-ARTHRITIS; ARTICULAR-CARTILAGE; CCN FAMILY; ARTHROPATHY; GENE; TARDA; DISORDER; CHONDROCYTES